Abiotic Stresses and Phytohormones Regulate Expression of FAD2 Gene in Arabidopsis thaliana - Si-wei YUAN; Xue-long WU; Zhi-hong LIU; Hong-bing LUO; Rui-zhi HUANG (Journal of Integrative Agriculture, 2012)
Modification of unsaturated fatty acid (FA) levels has been found to accompany multiple abiotic stress acclimations in many plants. Delta 12 fatty acid desaturase (FAD2) plays a critical role in the synthesis of polyunsaturated FAs in plant cells by converting oleic acid (18:1) to linoleic acid (18:2). To better understand the relationship between polyunsaturated FAs metabolism and stress adaptation, the expression of FAD2 gene and changes in the FA compositions under various abiotic stresses and phytohormone treatments in Arabidopsis thaliana was investigated in this study. A 1 423-bp promoter of the FAD2 gene was cloned and characterized from Arabidopsis. Several putative hormone- and stressinducible cis-elements were identified in the cloned promoter, which include salt- and pathogen-inducible GT-1 motifs, low-temperature-responsive MYC element, dehydration-responsive MYB element, and GA signaling related WRKY71OS element. To investigate the fine regulation of FAD2 gene, a recombinant FAD2 promoter-GUS construct was introduced into Arabidopsis plants. Histochemical study showed that the promoter was ubiquitously active and responsive not only to exogenous phytohormones including ABA, 24-eBL, and SA but also to darkness, temperature, salt, and sucrose stresses in Arabidopsis seedlings. Consistent with the expression change, treatments with exogenous 24-eBL, ABA, SA, and NaCl resulted in reduction in polyunsaturated FAs in Arabidopsis seedlings. These findings suggest that the FAD2 gene with a wide variety of putative response elements in its promoter is responsive to multiple phytohormones and abiotic stresses and therefore may play an important role in stress responses of Arabidopsis during plant growth and seed development.